PELAKSANAAN PROMOSI MAKANAN TRADISIONAL KHAS MELAYU DI HOTEL FURAYA PEKANBARU - Wahritasi "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to know the promotion mix of Malay Traditional Food and the response of visitor or society about the promotion mix which have been done by Hotel Furaya Pekanbaru management. The sample of this research is 150 people, taken by using accidental sampling techniques and key informant in this research consists of 3 people. This research format is survey the characteristic of this research is descriptive research. Based on the goals were achieved, this research uses qualitative method with triangulation method techniques as data validity test and quantitative method with the descriptive statistic technique and presentation of data in table format or frequency distribution in percentage as statement of the visitor response result. Results from this study is that the Hotel Furaya Pekanbaru management has done promotions by advertisements in newspapers, flyers and social media, sales promotion and personal selling. Based on the results of questionnaires, the positive response of respondents was most dominant in only three forms of media promotion, they are an online newspaper at statement item of the clarification on information and social media at the statement item about the use of understandable sentences. The remaining answers of the respondent’s statement stated that they were less agreed or not interested in the implementation performed.Keywords: Advertising, Sales Promotion, and Personal Selling